Theory of academic "lack of" knowledge. A map to "re-conceive" social sciences and the "newterritories" of communication - Bailón Maxi, Jaime (2009)
The new practices and communicative scenarios require a different way of representing reality. The objective of this article is to establish broad guidelines and execute a genealogy of important knowledge forms of the pase. This overview through the lineages of  knowledge develops, as a central thesis, a el ose linkage between the several knowledge forms and mechanisms o power in societies that have been suject of this study